2011
DOI: 10.1108/09600031111118549
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of product design changes on supply chain risk: a case study

Abstract: PurposeThe main purpose of this paper is to address the impact of product design changes on supply chain risk, and to identify the supply chain risk dimensions in the Chinese special‐purpose vehicle (SPV) industry in the context of product design change.Design/methodology/approachCase study methodology is adopted to describe the current situation of supply chain risk management in the Chinese SPV industry. Data are mainly collected from in‐depth semi‐structured interviews, and a cause‐effect diagram is used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
89
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 60 publications
1
89
0
5
Order By: Relevance
“…Therefore, this finding supports previous researches, which verified that the automotive industry is burdened by supply shortages (Trkman & McCormack, 2009;Snyder, 2011;Thun & Hoenig, 2011;Yong Lin & Li Zhou, 2011). When probing into this issue, this study found that importing automotive parts and components from Japan raised the risk of raw material shortage.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, this finding supports previous researches, which verified that the automotive industry is burdened by supply shortages (Trkman & McCormack, 2009;Snyder, 2011;Thun & Hoenig, 2011;Yong Lin & Li Zhou, 2011). When probing into this issue, this study found that importing automotive parts and components from Japan raised the risk of raw material shortage.…”
Section: Discussionsupporting
confidence: 89%
“…Regarding risk external to the firm but internal to the supply chain, previous researches revealed that quality of supplies received a greater deal of attention (Trkman & McCormack, 2009;Thun & Hoenig, 2011;Yong Lin & Li Zhou, 2011;Wagner & Neshat, 2012;Lockamy III & McCormack, 2012). Nevertheless, this study proves that only one of the case companies, the air-conditioner manufacturer, experienced this problem.…”
Section: Discussionmentioning
confidence: 59%
“…When looked into the country selection researchers have linked country context profile to the nature of supply chain risk, for example, Lin and Zhou (2011) note in their paper on supply chain risk based on the product design can be observed in developing countries, such as Brazil, China and India, which has also drawn interest from (Lin and Zhou, 2011) as the SCRM is relatively new in developing country context. Blos et al (2009).…”
Section: Global Distribution Of Supply Chain Risk Researchmentioning
confidence: 99%
“…Some studies tried to overcome this challenge with a comparative risk profile,while providing a risk risk focal area, i.e. specific region (Lin and Zhou, 2011). Lin and Zhou (2011) also note that the risk may also correlate to the increased number of global customers outsourcing their products to China.…”
Section: Global Distribution Of Supply Chain Risk Researchmentioning
confidence: 99%
See 1 more Smart Citation